Changes in hospital variation in the probability of receiving treatment with curative intent for esophageal and gastric cancer. (April 2021) - Luijten, Josianne C.H.B.M.; Vissers, Pauline A.J.; Lingsma, Hester; van Leeuwen, Nikki; Rozema, Tom; Siersema, Peter D.; Rosman, Camiel; van Laarhoven, Hanneke W.M.; Lemmens, Valery E.P.; Nieuwenhuijzen, Grard A.P.; Verhoeven, Rob H.A.
Highlights: Practice variation between hospitals of diagnosis decreased for esophageal cancer. Practice variation between hospitals remained stable for gastric cancer. A higher probability of curative treatment was associated with better survival. Abstract: Background: Previous studies describe a large variation in the proportion of patients undergoing treatment with curative intent for esophageal (EC) and gastric cancer (GC). Since centralization of surgical care was initiated and more awareness regarding hospital practice variation was potentially present, we hypothesized that hospital practice variation for potentially curable EC and GC patients changed over time. Methods: Patients with potentially curable EC (n = 10, 115) or GC (n = 3988) diagnosed between 2012–2017 were selected from the Netherlands Cancer Registry. Multilevel multivariable logistic regression was used to analyze the differences in the probability of treatment with curative intent between hospitals of diagnosis over time, comparing 2012−2014 with 2015−2017. Relative survival (RS) between hospitals with different probabilities of treatment with curative intent were compared. Results: The range of proportions of patients undergoing treatment with curative intent per hospital of diagnosis for EC was 45–95 % in 2012−2014 and 54–89 % in 2015−2017, and for GC 52–100 % and 45–100 %. The adjusted variation declined for EC with Odds Ratios ranging from 0.50 to 1.72 between centers in the first period to 0.70–1.44 in the second period (p < 0.001) and did not change for GC (Odds Ratios ranging from 0.78 to 1.23 to 0.82–1.23, (p = 1.00) ). A higher probability of treatment with curative intent was associated with a better survival for both malignancies. Conclusion: Although substantial variation between hospitals of diagnosis in the probability in receiving treatment with curative intent still exists for both malignancies, it has decreased for EC. A low probability of receiving curative treatment remained associated with worse survival.